Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0029090
|View full text |Cite
|
Sign up to set email alerts
|

Hybridogenesis in Water Frogs

Abstract: Several water frogs from the genus Pelophylax have a hybrid origin and perpetuate by hybridogenesis, a peculiar mode of reproduction ruled by complex phenomena such as clonality and polyploidy, and which can constitute a transient stage towards the formation of novel species. Different kinds of hybridogenetic complexes have been documented throughout Europe, and a tremendous diversity of breeding systems allows their maintenance in space and time, each with its own subtilities to by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…This complex matter was recently reviewed in a previous issue of this journal [159], and we will provide here one compelling case that illustrates how the lack of sex chromosome differentiation can open the path towards hybrid speciation, namely the hybridogenetic water frog system (genus Pelophylax ). These frogs are male heterogametic [155], and the hybrid taxon P. esculentus (genomes RL) was presumably formed by initial crossing between females P. ridibundus (genomes RR) and males P. lessonae (genomes LL). Hence, the Y chromosome is inherited with the L genome, while the X chromosome is inherited with the R genome.…”
Section: Perspectives For Speciation Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This complex matter was recently reviewed in a previous issue of this journal [159], and we will provide here one compelling case that illustrates how the lack of sex chromosome differentiation can open the path towards hybrid speciation, namely the hybridogenetic water frog system (genus Pelophylax ). These frogs are male heterogametic [155], and the hybrid taxon P. esculentus (genomes RL) was presumably formed by initial crossing between females P. ridibundus (genomes RR) and males P. lessonae (genomes LL). Hence, the Y chromosome is inherited with the L genome, while the X chromosome is inherited with the R genome.…”
Section: Perspectives For Speciation Researchmentioning
confidence: 99%
“…To do so, hybrid taxa often rely on peculiar mechanisms like hybridogenesis (e.g. Pelophylax [154,155]) and allopolyploidization (e.g. Bufotes [156,157]), which both involve the clonal transmission of one parental genome [156,158].…”
Section: (B) Consequences On the Mode Of Speciationmentioning
confidence: 99%
“…It hosts both natural and artificial ponds and lacks streams and water connections between ponds (Denoël and Ficetola 2014;Duret et al 2022). Genetic analyses have identified water frogs in the study area as P. ridibundus (Dufresnes et al 2017), a species also named Pelophylax fortis in Europe, according to debated nomenclatural revisions (Dufresnes and Mazepa 2020), but the traditional taxonomic assignment is used here until a decision is taken by the code of nomenclature. Two lineages have been identified in the study area, namely, the Balkan marsh frog (kurtmuelleri lineage) and the marsh frog (ridibundus lineage), which are both of nonindigenous origin (Dufresnes et al 2017).…”
Section: Study Area and Speciesmentioning
confidence: 99%
“…The most widespread taxon, the marsh frog (Pelophylax ridibundus), native to Central and Eastern Europe, was introduced multiple times in Western Europe for ornamental and culinary reasons where it is currently spreading broadly (Dufresnes et al 2018), and recognized as harmful invaders of aquatic ecosystems in many countries (Holsbeek et al 2008;Dubey et al 2014;Pagano et al 2001;Pille et al 2021). Invasive water frogs can eliminate the genome of native Pelophylax species through hybridogenesis, raising concerns about the preservation of the genetic integrity of native taxa (Dufresnes and Mazepa 2020). Nevertheless, the persistence of native species after water frog invasions suggests that the ecological divergence between native and invasive Pelophylax species is causing ecological isolation .…”
Section: Introductionmentioning
confidence: 99%
“…One previous genetic study identified marsh frogs in the studied area as lineages of Pelophylax ridibundus [26]. This species is also named Pelophylax fortis, according to debated nomenclatural revisions [49], but the traditional taxonomic assignment (i.e., P. ridibundus) is used here. Two morphologically cryptic lineages (the Balkan marsh frog P. kurtmuelleri and the marsh frog sensu stricto P. ridibundus) were genetically identified in Larzac populations, both of non-indigenous origin (i.e., from eastern/southeastern Europe [26]).…”
Section: Study Area and Organismsmentioning
confidence: 99%